Determining the optimal threonine: lysine ratio in starter diets for the segregated early-weaned pig - Bergstrom, J.R.; Owen, K.Q.; Richert, B.T.; Nessmith, W.B. Jr.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 35-day growth trial was conducted to determine the threonine: lysine ratio necessary to optimize growth performance of the segregated early-weaned (SEW) pig. Twelve experimental diets included two levels of lysine (1.15% and 1.5% digestible lysine) and six digestible threonine:lysine ratios (50, 55, 60, 65, 70, and 75%) in a 2 x 6 factorial arrangement. Growth performance was improved by feeding 1.5% digestible lysine, rather than 1. 15% digestible lysine. However, growth performance was not improved by increasing dietary threonine. These data indicate that the threonine requirement is no more than 50% of digestible lysine.
Keywords: Swine; Early-weaned pigs; Amino acids; Threonine